Construction and Validation of a T Cell Exhaustion–Related Prognostic Signature in Cholangiocarcinoma - Changshi Qian; Yuqiao Sun; Yihuai Yue (International Journal of Genomics)
Conclusion: A prognostic signature was developed by four TEX-related genes, including PALLD, RAB31, ADAMTS2, and WISP1, which might be a powerful predictor for the prognosis of patients with CCA. These TEX-related genes were related to the infiltration of neutrophils, endothelial cells, B cells, and T cells in CCA.